2021
DOI: 10.31234/osf.io/cyvwf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internet based language production research with overt articulation: Proof of concept, challenges, and practical advice

Abstract: Language production experiments with overt articulation have thus far only scarcely been conducted online, mostly due to technical difficulties related to measuring voice onset latencies. Especially the poor audiovisual synchrony in web experiments (Bridges et al., 2020) is a challenge to time-locking stimuli and participants’ spoken responses. We tested the viability of conducting language production experiments with overt articulation in online settings using the picture-word interference paradigm – a classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…In a picture-naming paradigm, Fairs & Strijkers (2021) replicated lab-based effects of word frequency in an online experiment run on the platform FindingFive (FindingFive Team, 2019) with 100 participants. For the picture word interference (PWI) effect (Bürki et al, 2020;Lupker, 1979), which requires naming object pictures overlayed with semantically related or unrelated distractor words, Vogt et al (2021) showed online-feasibility reproducing the lab-based findings. They implemented the experiment on two different platforms (jsPsych, de Leeuw & Motz, 2016;and SoSciSurvey, Leiner, 2019) with different participant cohorts (each n = 48).…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…In a picture-naming paradigm, Fairs & Strijkers (2021) replicated lab-based effects of word frequency in an online experiment run on the platform FindingFive (FindingFive Team, 2019) with 100 participants. For the picture word interference (PWI) effect (Bürki et al, 2020;Lupker, 1979), which requires naming object pictures overlayed with semantically related or unrelated distractor words, Vogt et al (2021) showed online-feasibility reproducing the lab-based findings. They implemented the experiment on two different platforms (jsPsych, de Leeuw & Motz, 2016;and SoSciSurvey, Leiner, 2019) with different participant cohorts (each n = 48).…”
mentioning
confidence: 68%
“…Recent evidence, however, suggests that studying language production via online platforms is possible. Overt naming responses acquired online have been demonstrated to be precise enough to detect speech-onset reaction time effects in the critical range of ~10-20 milliseconds (Fairs & Strijkers, 2021a;Vogt et al, 2021). In a picture-naming paradigm, Fairs & Strijkers (2021) replicated lab-based effects of word frequency in an online experiment run on the platform FindingFive (FindingFive Team, 2019) with 100 participants.…”
mentioning
confidence: 99%
See 3 more Smart Citations